Gender spillovers from supervisory boards to management boards - Viktor Bozhinov; Jasmin Joecks; Katrin Scharfenkamp (Managerial and Decision Economics, 2021)
This study investigates gender spillovers from women on supervisory boards to women on management boards in a two-tier system with employee codetermination. The supervisory board consists of a nominating committee mainly responsible for the appointment of directors in the management board. By combining similarity attraction theory with power theory, we predict that only female shareholder representatives who serve on the nominating committee drive the positive effect on the presence of women on management boards. The results of the correlated random effects models in a sample of 95 German codetermined and publicly listed companies (2009–2016) confirm the predicted relationship.
Keywords: 650